Hypertensive events after the initiation of contemporary cancer therapies for breast cancer control. (27th May 2022) - Carter, Rebecca R.; Chum, Aaron P.; Sanchez, Reynaldo; Guha, Avirup; Dey, Amit K.; Reinbolt, Raquel; Kim, Lisa; Otchere, Prince; Oppong‐Nkrumah, Oduro; Abraham, William T.; Lustberg, Maryam; Addison, Daniel
Abstract: Background: Contemporary therapies improve breast cancer (BC) outcomes. Yet, many of these therapies have been increasingly linked with serious cardiotoxicity, including reports of profound hypertension. Yet, the incidence, predictors, and impacts of these events are largely unknown. Methods: Leveraging two large U.S.‐based registries, the National Inpatient Sample (NIS) and the Food and Drug Administration Adverse Event Reporting System (FAERS) databases, we assessed the incidence, factors, and outcomes of hypertensive events among BC patients from 2007 to 2015. Differences in baseline characteristics, hypertension‐related discharges, and complications were examined over time. Further, we performed a disproportionality analysis using reporting‐odds‐ratios (ROR) to determine the association between individual BC drugs and hypertensive events. Utilizing an ROR cutoff of >1.0, we quantified associations by drug‐class, and individual drugs with the likelihood of excess hypertension. Results: Overall, there were 5, 464, 401 BC‐admissions, of which 46, 989 (0.8%) presented with hypertension. Hypertensive BC patients were older, and saw initially increased in‐hospital mortality, which equilibrated over time. The mean incidence of hypertension‐related admissions was 732 per 100, 000 among BC patients, versus 96 per 100, 000 among non‐cancer patients (RR 7.71, p  < 0.001). Moreover, in FAERS, those with hypertension versus other BC‐treatment side‐effects were more frequently hospitalized (40.1% vs. 36.7%, p  < 0.001), and were most commonly associated with chemotherapy (45.9%). Outside of Eribulin (ROR 3.36; 95% CI 1.37–8.22), no specific drug was associated with a higher reporting of hypertension; however, collectively BC drugs were associated with a higher odds of hypertension (ROR 1.66; 95% CI 1.09–2.53). Conclusions: BC therapies are associated with a substantial increase in limiting hypertension. Abstract : Leveraging two large U.S.‐based registries, the National Inpatient Sample (NIS) and the Food and Drug Administration Adverse Event Reporting System (FAERS) databases, we assessed the incidence, factors, and outcomes of hypertensive events among breast cancer patients from 2007‐2015. We found that breast cancer therapies associate with a substantial increase in limiting hypertension.